Non-neuronal cell-derived acetylcholine, a key modulator of the vascular endothelial function in health and disease - Sonobe, Takashi; Kakinuma, Yoshihiko (Frontiers in Cardiovascular Medicine, 2024)
Vascular endothelial cells play an important role in regulating peripheral circulation by modulating arterial tone in the microvasculature. Elevated intracellular Ca2+ levels are required in endothelial cells to induce smooth muscle relaxation via endothelium-dependent mechanisms such as nitric oxide production, prostacyclin, and endothelial cell hyperpolarization. It is well established that exogenous administration of acetylcholine can increase intracellular Ca2+ concentrations, followed by endothelium-dependent vasodilation. Although endogenous acetylcholine's regulation of vascular tone remains debatable, recent studies have reported that endogenously derived acetylcholine, but not neuronal cell-derived acetylcholine, is a key modulator of endothelial cell function. In this minireview, we summarize the current knowledge of the non-neuronal cholinergic system (NNCS) in vascular function, particularly vascular endothelial cell function, which contributes to blood pressure regulation. We also discuss the possible pathophysiological impact of endothelial NNCS, which may induce the development of vascular diseases due to endothelial dysfunction, and the potential of endothelial NNCS as a novel therapeutic target for endothelial dysfunction in the early stages of metabolic syndrome, diabetes, and hypertension.